Organizational patterns in the administration guidance services - Hatch, Raymond N.
The three topics reviewed here maybe identified as: the meaning of the term, educational leadership; the lack of functional organization in the administration of the school; and, lack of staff understanding of the various functions and roles to be played.
Keywords: Educational leadership; School management and organization; School personnel management; Counseling in education